DISCRIMINANT ANALYSIS OF FOOD SECURITY INDICATORS ACROSS THREE GEOPOLITICAL ZONES IN PLATEAU STATE, NIGERIA - Lumpye, Simji (FUDMA JOURNAL OF SCIENCES, 2025)
Food security remains a critical development concern in Plateau State, Nigeria, where diverse climatic conditions, recurrent conflicts, and socio-economic disparities have deepened household vulnerability to hunger and malnutrition. This study aimed to examine and classify food security indicators across the three geopolitical zones of Plateau State, which include the Northern, Central, and Southern Zones, using discriminant analysis. A cross-sectional survey design was adopted, and data were collected from 2,786 households selected through a multi-stage stratified random sampling technique. The structured questionnaire captured demographic, socio-economic, environmental, and food access variables. Descriptive statistics summarized the household characteristics, while discriminant analysis identified and compared key indicators that distinguish food-secure from food-insecure households across the zones. Results revealed significant inter-zonal variations in household food security, with income level, access to farmland, household size, and meal frequency emerging as the most discriminating variables. The findings demonstrate that food security in Plateau State is strongly shaped by both economic and environmental factors, which differ by region. The study concludes that targeted, zone-specific interventions are essential to addressing the underlying determinants of food insecurity. The application of discriminant analysis also contributes methodologically by offering a robust approach for regional classification in food security studies. These results provide evidence for policymakers and development planners to formulate data-driven strategies aligned with the Sustainable Development Goals, particularly Goals 1 (No Poverty) and 2 (Zero Hunger).